Response Of Ovarian And Uterine Morphological-Functional Features To Gonadotropins In Dexamethasone Treated Adult Mice - M. Ostaomar, Salma; M. El-Mansoury, Abdulla; R. Mehdi, Abdulwahab (Scientific Journal of University of Benghazi, 2026)
This study aimed at investigating the possibility of reversing the adverse effects, on the reproductive system, that are associated with the administration of synthetic glucocorticoids. Cycling Swiss albino mice were divided into four groups, 12 mice each. Control mice were daily intramuscularly injected with 0.1 ml normal physiological saline solution for ten days. Mice of the Gonadotropins group received six daily injections of 0.1 ml normal saline solution followed by three daily injections of the gonadotropins: 04 IU FSH activity on the seventh and ninth days, whereas 05 IU LH activity was administered on the tenth day. Mice of the Dexamethasone group were daily injected with 02 ug of the synthetic glucocorticoid for six days, followed by daily injections of 0.1 ml normal saline solution for four days. Animals of the Dexamethasone – Gonadotropins group were treated with Dexamethasone for the first six days followed by three daily injections of the Gonadotropins as described above. On the eleventh day, animals were euthanized with ether and weighed. Ovaries and uteri were dissected out, weighed and out into a tissue fixative solution to prepare stained sections.